Minimizing Tax Evasion That Harms the State Through Optimizing Taxpayer Behavioral Awareness - Ginting, Wahyudi Pialanta; Ginting, Chris Dayanti Br.; Said, Siti Nur Reskiyawati (Phinisi Applied Accounting Journal, 2025)
Tax evasion is one of the problems that often occurs in the implementation of taxation, including in Indonesia. Until now, there are still many cases of tax evasion due to the behavior of taxpayers who are not compliant with their tax obligations. This article aims to examine taxpayer behavior towards tax evasion. The literature review approach is used as a research method in writing this article. The article search was conducted through the google schoolar electronic database with the keyword tax evasion. From all the references that have been obtained, they are then selected according to the topics discussed. The results of the literature study indicate that an act of tax evasion is based on the level of rationality and the taxpayer's environment which will further determine the behavior of complying with or violating their tax obligations. In addition, the attitude of tax non-compliance and tax evasion is also motivated by several factors, namely the tax system, justice, discrimination and fraud detection will lead to a person's attitude to disobey and will embezzle taxes on his obligations.Penggelapan pajak merupakan salah satu permasalahan yang sering terjadi dalam penyelenggaraan perpajakan termasuk di Indonesia. Hingga saat ini masih banyak terjadi kasus penggelapan pajak dikarenakan perilaku dari wajib pajak  yang tidak patuh atas kewajiban perpajakannya. Artikel ini bertujuan untuk mengkaji perilaku wajib pajak terhadap penggelapan pajak. Pendekatan literature review digunakan sebagai metode penelitian dalam penulisan artikel ini. Pencarian artikel tersebut dilakukan melalui database elektronik google schoolar dengan kata kunci penggelapan pajak (tax evasion). Dari semua referensi yang telah didapat kemudian diseleksi sesuai topik yang dibahas. Hasil studi literatur menunjukkan bahwa suatu tindakan penggelapan pajak di dasari oleh adanya tingkat rasionalitas dan lingkungan wajib pajak yang selanjutnya akan menentukan perilaku patuh atau melanggar kewajiban perpajakannya. Selain itu, sikap ketidakpatuhan pajak dan penggelapan pajak juga dilatarbelakangi oleh beberapa faktor yakni sistem perpajakan, keadilan, diskriminasi dan deteksi kecurangan akan menimbulkan sikap seseorang untuk tidak patuh dan akan menggelapkan pajak atas kewajibannya.